18F-fluciclovine PET-CT and 68Ga-PSMA-11 PET-CT in patients with early biochemical recurrence after prostatectomy: a prospective, single-centre, single-arm, comparative imaging trial. Issue 9 (September 2019) - Calais, Jeremie; Ceci, Francesco; Eiber, Matthias; Hope, Thomas A; Hofman, Michael S; Rischpler, Christoph; Bach-Gansmo, Tore; Nanni, Cristina; Savir-Baruch, Bital; Elashoff, David; Grogan, Tristan; Dahlbom, Magnus; et al.
Summary: Background: National Comprehensive Cancer Network guidelines consider 18 F-fluciclovine PET-CT for prostate cancer biochemical recurrence localisation after radical prostatectomy, whereas European Association of Urology guidelines recommend prostate-specific membrane antigen (PSMA) PET-CT. To the best of our knowledge, no prospective head-to-head comparison between these tests has been done so far. The aim of this study was to compare prospectively paired 18 F-fluciclovine and PSMA PET-CT scans for localising biochemical recurrence of prostate cancer after radical prostatectomy in patients with low prostate-specific antigen (PSA) concentrations (<2·0 ng/mL). Methods: This was a prospective, single-centre, open-label, single-arm comparative study done at University of California Los Angeles (Los Angeles, CA, USA). Patients older than 18 years of age with prostate cancer biochemical recurrence after radical prostatectomy and PSA levels ranging from 0·2 to 2·0 ng/mL without any prior salvage therapy and with a Karnofsky performance status of at least 50 were eligible. Patients underwent 18 F-fluciclovine (reference test) and PSMA (index test) PET-CT scans within 15 days. Detection rate of biochemical recurrence at the patient level and by anatomical region was the primary endpoint. A statistical power analysis demonstrated that a sample size of 50 patients was needed to show a 22% difference in detection rates in favour of PSMA (test for superiority). Each PET scan was interpreted by three independent masked readers and a consensus majority interpretation was generated (two vs one) to determine positive findings. This study is registered with ClinicalTrials.gov, number NCT03515577, and is complete. Findings: Between Feb 26, 2018, and Sept 20, 2018, 143 patients were screened for eligibility, of whom 50 patients were enrolled into the study. Median follow-up was 8 months (IQR 7–9). The primary endpoint was met; detection rates were significantly lower with 18 F-fluciclovine PET-CT (13 [26%; 95% CI 15–40] of 50) than with PSMA PET-CT (28 [56%; 41–70] of 50), with an odds ratio (OR) of 4·8 (95% CI 1·6–19·2; p=0·0026) at the patient level; in the subanalysis of the pelvic nodes region (four [8%; 2–19] with 18 F-fluciclovine vs 15 [30%; 18–45] with PSMA PET-CT; OR 12·0 [1·8–513·0], p=0·0034); and in the subanalysis of any extrapelvic lesions (none [0%; 0–6] vs eight [16%; 7–29]; OR non-estimable [95% CI non-estimable], p=0·0078). Interpretation: With higher detection rates, PSMA should be the PET tracer of choice when PET-CT imaging is considered for subsequent treatment management decisions in patients with prostate cancer and biochemical recurrence after radical prostatectomy and low PSA concentrations (≤2·0 ng/mL). Further research is needed to investigate whether higher detection rates translate into improved oncological outcomes. Funding: None.